Gambaran Self-Confidence Remaja Yang Tinggal Di Panti Asuhan Kecamatan ÔÇ£XÔÇØ - Husna, Hafizhah Al (Batanang : Jurnal Psikologi, 2022)
This study aims to determine the self-confidence of adolescents who live in orphanages. This type of research uses a quantitative approach with descriptive techniques. The total population in this study were all teenagers living in the ÔÇ£XÔÇØ orphanage, which were 73 people. The sample selection technique in this study was a saturated sampling technique (census), that is, all youth orphanages in ÔÇ£XÔÇØ sub-district were sampled in the study. The data collection method uses a Likert scale which is distributed directly to teenagers who live in the ÔÇ£XÔÇØ District Orphanage. The data that has been collected is then processed using statistical analysis with the help of SPSS Version 26 software. The results of this study are seen based on the aspects of self-confidence which show that the self-confidence of adolescents living in the ÔÇ£XÔÇØ orphanage is in the high category as evidenced by the percentage by 43.8%. This means that teenagers who live in the ÔÇ£XÔÇØ District Orphanage have high self-confidence, then it have positive impact for activity.Keywords: self-confidence, adolescent, orphane